A Case Series to Evaluate the Efficacy of Kriyakalpa in Different Netravikaras (AYUSHDHARA, 2025)
Stye is an infection of the sebaceous glands of zeis at the base of the eye lashes, or an infection of the apocrine glands of moll. In Ayurvedic science, based on clinical signs and symptoms, stye can be correlated to Anjananamika. Abhisyanda, a Sarvagata netra roga is due to the immunological responses resulting in the inflammation of conjunctiva. The condition can be correlated to allergic conjunctivitis. Timira is mentioned under Drishtigatas rogas, in the present case it is considered as Dwitheeya patalagata timira and based on the signs and symptoms it can be correlated to that of the symptoms of presbyopia. Objectives are to evaluate the therapeutic effect of Kriyakalpas like Seka, Aschyotana, Bidalaka, Tarpana in the management of different Netra vikaras like Anjananamika w.s.r.to stye, Abhishyanda w.s.r. to allergic conjunctivitis, Timira w.s.r. to presbyopia. Methods: Three different cases were taken to evaluate the efficacies of Kriyakalpas which were done using different Dravyas for a specific time interval. The effect of treatment was assessed based on objective and subjective parameters before and after treatment. Results: On comparing the symptoms before and after treatment, there were significant changes noticed on both subjective and objective parameters. Interpretation & Conclusion: Kriyakalpas like Seka, Aschyotana, Bidalaka, Tarpana are the effective treatment modalities which can be adopted in the management of different Netra vikaras like Anjananamika w.s.r. to stye, Abhishyanda w.s.r. to allergic conjunctivitis, Timira w.s.r. to presbyopia.